Recovery and processing of 3D images in X-ray tomography - Syryamkin, Vladimir; Glushkov, Gleb; Bogomolov, Evgeniy; Brazovsky, Vasily (British Journal of Healthcare and Medical Research, 2014)
The article is to study operating procedures of an X-ray micro tomographic scanner, and the module of reconstrusction and analysis 3D-image of the test sample in particular. An algorithm for 3D-image reconstruction based on the image shadow projections and mathematical methods of the processing are described. Chapter 1 describes the basic principles of X-ray tomography, general procedures of the device developed. Chapter 2 and 3 are devoted to the problem of resources saving by the system during the X-ray tomography procedure, what is achieved by preprocessing of the initial shadow projections. Preprocessing includes background noise removing from the images, which reduces the amount of shadow projections in general and increases the efficiency of the group shadow projections compression. Chapter 4 covers general procedures of defect search, which is based on the vector analysis principles. In conclusion, the main applications of X-ray tomography are presented.